GURU MASA DEPAN DENGAN TEKNOLOGI PEMBELAJARAN BERBASIS HYBRID LEARNING MENUJU ERA SOCIETY 5.0 - Zaharah .; Ibnu Sina; Abdul Basyit; Khoirul Anwar; R Tommy Gumelar (Universitas Muhammadiyah Tangerang, 2023)
ABSTRACTHybrid learning-based learning technology is currently needed and also in the future.Education in the Society 5.0 era is a response to the needs of the human industrial revolution and technology to be aligned to create new creative and innovative opportunities.Teachers in facing the challenges of the Society 5.0 era must have adequate competence, teachers have a very strategic role in the development of students' movements.This is different from the education system of the past which only focused on producing educated workers with low salaries.Today's education focuses more on giving birth to a generation that is capable of creating change, not a generation that waits for change.The existence of this learning system certainly needs to be paid attention to because not all learning is suitable and suitable to be applied at this time, especially whether the teacher's ability is qualified or not because learning based on Hybrid learning requires mastery of technology for teachers and students in facing the Era of Society 5.0.Learning technology-based educational platforms as a means of supporting the improvement of future learning processes in an effort to improve the quality of primary, secondary and tertiary education.